Diagnosing of Radio-Electronic Equipment With the Help of Traditional CAD Systems - Kasyan, K.; Kasyan, N. (2006 International Conference - Modern Problems of Radio Engineering, Telecommunications, and Computer Science : February 28 2006-March 4 2006, 2006)
In this paper the approach to an actual problem of the automated diagnosing the radio-electronic equipment with use already existing CAD systems, therefore at rather small expenses the program system which covers not only a design stage of radio equipment, and its full life cycle turns out.